2013
DOI: 10.1186/1471-2407-13-469
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 promotes hepatocellular carcinoma HepG2 cell proliferation through repression of mitogen-activated protein kinase-kinase 3

Abstract: BackgroundmicroRNA 21 (miR-21) has been demonstrated to be significantly elevated in many types of cancers, including the hepatocellular carcinoma (HCC). In the present study, we investigated the role of miR-21 in HCC by identifying its novel targets, as well as its underlying molecular mechanism.MethodsThe expression of mitogen-activated protein kinase-kinase 3 (MAP2K3) in human HCC tumor tissues and adjacent non-tumor tissues was determined by immunohistochemistry staining (IHC) analysis. The 3’-untranslated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 40 publications
2
55
0
1
Order By: Relevance
“…In particular, miR-21 has been shown to be involved in various cancer-associated processes, including cell growth, invasion and apoptosis (14). miR-21 induces hepatocellular carcinoma HepG2 cell proliferation via the suppression of mitogen-activated protein kinase-kinase 3 (15). In addition, miR-21 promotes oral cancer invasion via the Wnt/β-catenin pathway by targeting DKK2 (16).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR-21 has been shown to be involved in various cancer-associated processes, including cell growth, invasion and apoptosis (14). miR-21 induces hepatocellular carcinoma HepG2 cell proliferation via the suppression of mitogen-activated protein kinase-kinase 3 (15). In addition, miR-21 promotes oral cancer invasion via the Wnt/β-catenin pathway by targeting DKK2 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Mice homozygous for miR-21 deletion are fertile and appear phenotypically normal, indicating that miR-21 is dispensable under normal physiologic conditions, yet plays a pivotal prosurvival function during cellular oncogenic transformation (11,12). In addition, a number of studies have demonstrated antiproliferative and antimigratory effects of miR-21 inhibitors in cancer cell lines in vitro (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have supported the hypothesis that miR-21 overexpression might promote HCC invasion and metastasis through direct or indirect mechanisms, and thus lead to poor prognosis (Liu et al, 2010;Tomimaru et al, 2010;Xu et al, 2011;Tomimaru et al, 2012;Zhu et al, 2012). Zhou et al (2013) demonstrated that miR-21 promoted side population cell migration and invasion by targeting PTEN, RECK, and PDCD4, and that it could also directly target MAP2K3 and inhibit its expression during HCC carcinogenesis (Xu et al, 2013). Therefore, patients with high tumoral miRNA-21 expression were shown to have a significantly shorter time-to-recurrence compared to those with low tumoral expression, and that patients with low plasma miRNA-21 expression tended to have a longer time-to-recurrence compared to those with high plasma miRNA-21 expression (Tomimaru et al, 2012).…”
Section: Discussionmentioning
confidence: 99%